[OP.6A.02] 24-HOUR SYSTOLIC BLOOD PRESSURE LOAD REPRESENTS AN IMPORTANT VARIABLE IN DETERMINING THE CARDIOVASCULAR RIK PROFILE OF WHITE-COAT HYPERTENSION. (September 2017) - Tadic, M.; Bombelli, M.; Villa, P.; Macchiarulo, M.; Gardini, M.; Parma, L.O.; Nicoli, F.; Scotton, E.; Facchetti, R.; Mancia, G.; Grassi, G.
Abstract : Objective: White-coat hypertension (WCH) displays an increased cardiovascular (CV) risk. Scanty are the data available on the impact of 24-hour average blood pressure (BP) load on the increased CV risk in this condition. Design and method: 2051 subjects randomly selected from the general population of Monza (Italy), aged 25 to 74 years, stratified for sex and decades of age, underwent measurement of systolic (S) and diastolic (D) office BP and average 24-hour ambulatory SBP and DBP. Anthropometric variables, serum cholesterol, blood glucose were also measured. During a median follow-up of 156 months hospital admissions for coronary and stroke events were collected. Fatal events were also collected, among which those related to CV causes (ICD-10 from I-0 to I-99) were identified. In the whole population sample, the subjects with both normal office BP (<140/90 mmHg) and normal 24-hour BP (<125/79 mmHg) were defined as normotensives (NT, n. 1001). Among the 356 subjects with high office BP and normal 24-hour BP (WCH), those with 24-hour SBP above and under the median value (118 mmHg) were classified as WCHH and WCHL, respectively. Results: The analysis was carried out on the 1001 NT and on the 356 WCH subjects. During the follow-up 112 deaths and 73 fatal and non fatal CV events. Total mortality was 5.7%, 20.8% and 10.1% in NT, WCHH and WCHL, respectively. Incidence of CV events was 3.4%, 14.6% and 7.3%, in NT, WCHH and WCHL, respectively. Adjusting the data for age, sex, hypercholesterolemia, diabetes mellitus, smoking, obesity, previous CV events and antihypertensive therapy, the risk of all cause death and CV events in WCHH was significantly higher than that of NT (HR 1.8, CI 1.2–2.8, and HR 2.7, CI 1.6–4.7, respectively; p < 0.01 for both). No significant difference was found in the CV risk between WCHL and NT. Conclusions: Although by definition in the normal range, the level of 24-hour ambulatory SBP load is a relevant factor in determining the enhanced CV risk in WCH. Indeed, when the 24-hour SBP values are low, the CV risk of WCH is not different from that displayed by NT.